The Dilemma Methodological Individualism against Methodological Holism in the Economic Science - Prodanov, Vasil (Research Papers, 2018)
The main goal of the study is to reveal a basic dilemma on the basis of which could be distinguished the methodologies of different economic theories. The dilemma methodological individualism – methodological holism has a leading role because it is connected with the most important characteristics of the starting point of the economic research. The development of these two methodologies is considered and how they become preconditions of mainstream or heterodox economic theories.
Keywords: Methodological holism; Dilemma; Methodological individualism